2018
DOI: 10.1021/acsabm.8b00236
|View full text |Cite
|
Sign up to set email alerts
|

Single or Mixed Tethered Peptides To Promote hMSC Differentiation toward Osteoblastic Lineage

Abstract: The commitment and differentiation of human mesenchymal stem cells (hMSCs) are guided by bioactive molecules within the extracellular matrix. Among the various approaches to design biomaterials, the functionalization of biomaterial surfaces with peptides from the sequence of proteins from the extracellular matrix is quite common. The purpose of this functionalization is to recruit hMSCs and promote their differentiation into the appropriate lineage. The aim of this work was to investigate the influence of RGD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(62 citation statements)
references
References 41 publications
4
56
0
Order By: Relevance
“…As polyacrylamide‐based materials do not support cell adhesion, [ 29,30 ] these hydrogels have been functionalized with a mimetic peptide of the bone morphogenetic protein‐2 (BMP‐2), which corresponds to residues 73–92 of BMP‐2 and has been shown to induce hMSCs osteoblast differentiation when grafted onto different materials (glass, polyethylene terephthalate, poly(acrylamide‐ co ‐acrylic acid) hydrogel). [ 69–73 ] Hydrogels functionalization has been assessed by using fluorescently labeled BMP‐2 peptide and by following previously described protocols. [ 69,71–73 ] It has been found that the fluorescence intensity on the surface of the two hydrogels with low and high relaxation is similar (data not shown), indicating that the peptide density lies within the same range between the two hydrogels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As polyacrylamide‐based materials do not support cell adhesion, [ 29,30 ] these hydrogels have been functionalized with a mimetic peptide of the bone morphogenetic protein‐2 (BMP‐2), which corresponds to residues 73–92 of BMP‐2 and has been shown to induce hMSCs osteoblast differentiation when grafted onto different materials (glass, polyethylene terephthalate, poly(acrylamide‐ co ‐acrylic acid) hydrogel). [ 69–73 ] Hydrogels functionalization has been assessed by using fluorescently labeled BMP‐2 peptide and by following previously described protocols. [ 69,71–73 ] It has been found that the fluorescence intensity on the surface of the two hydrogels with low and high relaxation is similar (data not shown), indicating that the peptide density lies within the same range between the two hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…[ 69–73 ] Hydrogels functionalization has been assessed by using fluorescently labeled BMP‐2 peptide and by following previously described protocols. [ 69,71–73 ] It has been found that the fluorescence intensity on the surface of the two hydrogels with low and high relaxation is similar (data not shown), indicating that the peptide density lies within the same range between the two hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies take advantage of only the sequence responsible for the osteogenic activity of this molecule to functionalize biomaterials for bone tissue engineering applications [19,32,33]. The combination of a peptide promoting cell adhesion with one promoting cell differentiation for the co-functionalization of a biomaterial has been reported to further enhance differentiation when compared with the grafting of only one peptide sequence, such as a BMP-2 mimetic peptide [34][35][36][37][38]. Several studies can be found reporting also synergistic effects of combining nanotopographies with chemical cues on osteogenic differentiation of hMSCs or osteoblast progenitors [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…This latter approach is based on the immobilization of a cocktail of biomolecules, thus implicitly complexifying the issue related to biomolecule immobilization. [8] Various routes are already reported for the multifunctionalization of surfaces, namely (a) the successive immersion, generally in overestimated durations, of a single surface in different biomolecule-containing solutions [9] ; (b) the single immersion of a surface in a solution containing a mixture of biomolecules [10] ; and (c) the immobilization of synthetic and multifunctional biomolecules, also known as fusion proteins. [11] More importantly, most biomaterial surfaces lack chemical reactive sites, thus limiting their potential for biomolecule covalent modifications toward the development of functional coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Various routes are already reported for the multifunctionalization of surfaces, namely (a) the successive immersion, generally in overestimated durations, of a single surface in different biomolecule‐containing solutions [ 9 ] ; (b) the single immersion of a surface in a solution containing a mixture of biomolecules [ 10 ] ; and (c) the immobilization of synthetic and multifunctional biomolecules, also known as fusion proteins. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%